Alleviative mechanism and effect of Bifidobacterium animalis A6 on dextran sodium sulfate‐induced ulcerative colitis in mice. Issue 2 (9th November 2022) - Wu, Fang; Wuri, Guna; Fang, Bing; Shi, Mengxuan; Zhang, Ming; Zhao, Liang
Abstract: Probiotics have been increasingly investigated for their role in alleviating symptoms of ulcerative colitis (UC), but the specific mechanism involved remains unclear. We investigated the alleviating effect of Bifidobacterium animalis A6 (BAA6) in UC through a mouse dextran sulfate sodium (DSS) model. When treated with a high dose of BAA6 (1 × 10 10  cfu/ml), it was found that colitis symptoms were significantly alleviated, and mucosal damages experienced obvious relief. Moreover, a high dose of BAA6 effectively upregulated free fatty acid receptors 2 and 3 (FFAR2 and FFAR3) expression and butyric acid metabolism specifically. Furthermore, the supplement of BAA6 significantly suppressed pro‐inflammatory cytokines levels (interleukin‐13) and the expression of pore‐forming protein claudin‐2. The upstream regulatory genes of claudin‐2, such as STAT6, GATA4, Cdx2, were also significantly inhibited by BAA6. Collectively, this study concludes that BAA6 attenuated DSS‐induced colitis by increasing the levels of intestinal butyric acid, activating the butyric acid‐FFAR pathway, suppressing excessive proinflammatory response, and protecting the function of the colon epithelial barrier. Abstract : This study suggested that Bifidobacterium animalis A6 attenuated DSS‐induced colitis by increasing the levels of intestinal butyric acid, activating the butyric acid‐FFAR pathway, suppressing excessive proinflammatory response, and protecting colon epithelial barrier function.